High-order LES of the flow over a simplified car model: On the influence of the Reynolds number - Minguez, Matthieu; Pasquetti, Richard; Serre, Eric (European Journal of Computational Mechanics, 2009)
We study the influence of the Reynolds number on the Ahmed body flow for the subcritical incidence . =25°. Large Eddy Simulations (LES) have been performed at low Reynolds number Re=8322, in agreement with the experiments of Spohn and Gillieron (2002), for the configuration used by Lienhart et al. (2002) at Re=768000. Our simulations, based on a spectral Chebyshev collocation-Galerkin Fourier method, have been carried out with a parallel multi-domain solver. The LES capability is implemented by a Spectral Vanishing Viscosity (SVV) technique. The results globally point out that the topology of the flow is essentially determined by the body geometry.